Redefinition of International Peace in the Use of Outer Space Based on Peacefull Purpose Principle in Outer Space Treaty 1967 - Tandungan, Edmondus Sadesto; Salim, Andre; Christy, Gracesy Prisela (International Journal of Law Reconstruction, 2025)
The 1967 Outer Space Treaty was established as a basis for the peaceful exploration and use of outer space. However, since its inception, there has been no standard definition of the phrase "peaceful purpose" in the 1967 Outer Space Treaty. Differences in interpretation regarding the peaceful purpose of using outer space have given rise to differences in space exploration actions by several countries which could actually threaten international peace. The aim of this writing is to redefine the concept of international peace in 1967 Outer Space Treaty. This type of research is normative legal research by examining the Outer Space Treaty and various concepts in international law, particularly regarding the concept of international peace. The data used is secondary data in the form of primary legal materials and secondary legal materials. The primary legal material used is the provisions on the use of outer space in the 1967 Outer Space Treaty and the United Nations Charter, while the secondary legal material consists of various literature related to the topic under study. The data obtained was then analyzed qualitatively using deductive thinking methods. The research results show that international peace in the use of outer space is defined as eliminating all forms of threats that have the potential to cause conflict between countries, where outer space may not be used for any military purposes.